Complex optimization of the remote gamma-irradiation process mustafa m. E. Taha - M. E. TAHA, Mustafa (Biophysical Bulletin)
The problem of complex optimization of the remote gamma-irradiation process was considered. The formalized model of the process was proposed. The control factors were indicated. The selection of values of the factors provides obtaining of the given irradiation doses under the minimum side effect. The proposed method allows to provide the more favourable conditions at the expense of more complete irradiation scheme, number and arrangement of the irradiation equipment, and also using of screen diaphragm and more accurate selection of its placing.